Economics and Politics of the Public-Private Wage Gap (The Case of Russia) - Vladimir Gimpelson; Anna Lukiyanova; Anna Sharunina (Institute of Labor Economics (IZA), 2019)
The paper explores the public-private wage gap in the Russian economy over time and along the whole wage distribution. Using the RLMS-HSE panel data set, we examine how gaps at various points of wage distribution changed from 2005 to 2015 and present decompositions of the gaps into components explained by differences in characteristics and differences in returns. The results suggest that the gap persists over time and varies along the wage distribution. During the 2000's, low-skilled public sector workers had smaller pay gaps than higher-skilled workers had. Multiple governmental policy interventions and the economic crisis of 2008-2009 contributed to the narrowing of the gap and its partial equalization along the distribution. A new set of policy changes associated with the May 2012 Presidential Decrees strengthened these tendencies but failed to eliminate the gaps.
Keywords: J31; J45; 330; public sector; public-private wage gap; quantile regression; RLMS-HSE; Russia